Image_1_The Increased Expression of an Engrailed to Sustain Shell Formation in Response to Ocean Acidification.JPEG - Yukun Zhang; Zhaoqun Liu; Yanan Zong; Yan Zheng; Yinan Li; Zirong Han; Lingling Wang; Linsheng Song (2020)
Engrailed is a transcription factor required in numerous species for important developmental steps such as neurogenesis, segment formation, preblastoderm organization, and compartment formation. Recent study has proved that engrailed is also a key gene related to shell formation in marine bivalves. In the present study, the expression pattern of an engrailed gene (Cgengrailed-1) in Pacific oyster Crassostrea gigas under CO 2 -driven acidification was investigated to understand its possible role in the regulation of shell formation and adaptation to ocean acidification (OA). The open reading frame (ORF) of Cgengrailed-1 was obtained, which was of 690 bp encoding a polypeptide of 229 amino acids with a HOX domain. Phylogenetic analysis indicated that the deduced amino acid sequence of Cgengrailed-1 shared high homology with other engraileds from Drosophila melanogaster, Mizuhopecten yessoensi, and Crassostrea virginica. The mRNA transcripts of Cgengrailed-1 were constitutively expressed in various tissues with the highest expression levels detected in labial palp and mantle, which were 86.83-fold (p < 0.05) and 75.87-fold (p < 0.05) higher than that in hepatopancreas. The mRNA expression of Cgengrailed-1 in mantle decreased dramatically after moderate (pH 7.8) and severe (pH 7.4) acidification treatment (0.75- and 0.15-fold of that in control group, p < 0.05). The results of immunofluorescence assay demonstrated that the expression level of Cgengrailed-1 in the middle fold of mantle increased significantly upon moderate and severe acidification treatment. Moreover, after the oyster larvae received acidification treatment at trochophore stage, the mRNA expression levels of Cgengrailed-1 increased significantly in D-shape larvae stages, which was 3.11- (pH 7.8) and 4.39-fold (pH 7.4) of that in control group (p < 0.05). The whole-mount immunofluorescence assay showed that Cgengrailed-1 was mainly expressed on the margin of shell gland, and the periostracum in trochophore, early D-shape larvae and D-shape ...